ASSOCIATION BETWEEN HISTORY OF LOW BIRTH WEIGHT (LBW) AND STUNTING INCIDENCE AMONG CHILDREN AGED 24–60 MONTHS - Apriliana, Dini; Azizah, Nur; Muhidayati, Wiwik (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Stunting is a chronic growth disorder caused by prolonged malnutrition and recurrent infections. One of the main risk factors for stunting is a history of Low Birth Weight (LBW). This study aims to determine the relationship between LBW history and the incidence of stunting among children aged 24–60 months in the working area of Balen Public Health Center, Bojonegoro Regency, in 2025.  Method: This research used a case-control study design with a quantitative approach. The population consisted of all children aged 24–60 months in the area. Sampling was conducted using total sampling for the case group and purposive sampling for the control group. Data were collected through measurements and interviews using a structured questionnaire, and analyzed using the Spearman Rho test. Result: The results showed a significant relationship between LBW history and stunting, with a p-value of 0.044 (p < 0.05). Children with a history of LBW were at higher risk of experiencing stunting compared to those born with normal birth weight. Conclusion : In conclusion, LBW history is a significant risk factor for stunting. Preventive efforts should include prenatal monitoring, maternal nutrition education, and early intervention for LBW infants to reduce the risk of stunting.